Hitler inspects a guard of 500 Italian veterans accompanied by Adolf Wagner (to his left) and Carlo Delcroix (behind him) at the "Königlichen Platz" in Munich. Text on the back
Hitler inspects a guard of 500 Italian veterans accompanied by Adolf Wagner (to his left) and Carlo Delcroix (behind him) at the "Königlichen Platz" in Munich. Text on the back.